Transluminal endoscopic necrosectomy: revisited from the surgeon's perspective - Hartwig, Werner; Werner, Jens; Büchler, Markus W. (Gut, 2010)
In a retrospective analysis of 93 patients, Seifert et al 1 investigated the role of transluminal endoscopic necrosectomy after acute pancreatitis. From the authors' point of view, the mortality rate of only 7.5% and a good long-term outcome appear to make this relatively new approach look favourable when compared with the results of published studies on surgical debridement in necrotising pancreatitis. However, a detailed look at the characteristics of the patients in the GEPARD study shows that this is like comparing apples and oranges. Surgical series on acute pancreatitis predominantly investigate the subset of patients with infected necrosis and severe organ dysfunction. Data on the severity of …